FOOD ACCEPTANCE IN DIFFERENT LARVAL STAGES OF Macrobrachium carcinus - Cassia Barbosa CONSTANTINIDIS; Mariana Cutolo de ARAUJO (Boletim do Instituto de Pesca)
Food acceptance in different larval stages of Macrobrachium carcinus was evaluated by investigating the stage at which the ingestion of inert moist diet food begins and by the incidence of Artemia nauplii and inert moist diet in the digestive tract throughout development. Two experiments were carried out: in the first study, the acceptance of the inert diet was evaluated in 60 larvae of each stage (I to XII) fed ad libitum after two hours of fasting. The inert diet was 100% accepted at zoea stage V. In the second study, newly hatched larva was then kept in larval tanks and fed with Artemia nauplii and inert moist diet simultaneously. Fifteen minutes after feeding, 50 specimens of each larval stage were examined and evaluated for the ingestion of these foods. Larvae at stage I did not feed, while larvae at stage II consumed both live and inert food. From the stage of zoea IX, the exclusive consumption of Artemia nauplii was not verified. These data indicate that feeding M. carcinus in larviculture can be initiated at stage II with inert moist diet and Artemia nauplii, and an exclusive supply of inert moist diet from stage IX can be recommended.